Distinct gut microbiota profiles in patients with primary sclerosing cholangitis and ulcerative colitis - Bajer, Lukas; Kverka, Miloslav; Kostovcik, Martin; Macinga, Peter; Dvorak, Jiri; Stehlikova, Zuzana; Brezina, Jan; Wohl, Pavel; Spicak, Julius; Drastich, Pavel (World journal of gastroenterology, 2017)
AIM: To characterize the gut bacterial microbiota of patients with primary sclerosing cholangitis (PSC) and ulcerative colitis (UC). METHODS: Stool samples were collected and relevant clinical data obtained from 106 study participants, 43 PSC patients with (n = 32) or without (n = 11) concomitant inflammatory bowel disease, 32 UC patients, and 31 healthy controls. The V3 and V4 regions of the 16S ribosomal RNA gene were sequenced on Illumina MiSeq platform to cover low taxonomic levels. Data were further processed in QIIME employing MaAsLin and LEfSe tools for analysis of the output data. RESULTS: Microbial profiles in both PSC and UC were characterized by low bacterial diversity and significant change in global microbial composition. Rothia, Enterococcus, Streptococcus, Veillonella, and three other genera were markedly overrepresented in PSC regardless of concomitant inflammatory bowel disease (IBD). Rothia, Veillonella and Streptococcus were tracked to the species level to identify Rothia mucilaginosa, Streptococcus infantus, S. alactolyticus, and S. equi along with Veillonella parvula and V. dispar. PSC was further characterized by decreased abundance of Adlercreutzia equolifaciens and Prevotella copri. Decrease in genus Phascolarctobacterium was linked to presence of colonic inflammation regardless of IBD phenotype. Akkermansia muciniphila, Butyricicoccus pullicaecorum and Clostridium colinum were decreased in UC along with genus Roseburia. Low levels of serum albumin were significantly correlated with enrichment of order Actinomycetales. CONCLUSION: PSC is associated with specific gut microbes independently of concomitant IBD and several bacterial taxa clearly distinguish IBD phenotypes (PSC-IBD and UC).
Keywords: dospělí; Intestinal Mucosa; kolon; sekvenční analýza RNA; Healthy Volunteers; Female; feces; Feces; Adult; ženské pohlaví; Gastrointestinal Microbiome; zdraví dobrovolníci pro lékařské studie; RNA, Ribosomal, 16S; Colon; sklerozující cholangitida; lidé; Cholangitis, Sclerosing; Colitis, Ulcerative; Dysbiosis; Male; Aged; Bacteria; střevní mikroflóra; dysbióza; ulcerózní kolitida; Sequence Analysis, RNA; lidé středního věku; senioři; mužské pohlaví; Middle Aged; RNA ribozomální 16S; střevní sliznice; Humans